Book Reviews (Journal of Finance, 1992)
Book reviewed in this article: The Economics of Mutual Fund Markets: Competition Versus Regulation . By WILLIAM BAUMOL, STEPHEN GOLDFELD, LILLI GORDON, and MICHEAL KOEHN. Boston: Kluwer Academic Publishers, 1990. Pp. xiv + 242. The Great Myths of 1929 and the Lessons to be Learned . By HAROLD BIERMAN, Jr. New York: Greenwood Press, 1991. Pp. xii + 203. Currency Risk and Business—Management . By ALFRED KENYON. Oxford: Basil Blackwell, 1990. Pp. vi + 260. The Future of Banking . By JAMES L. PIERCE. New Haven: Yale University Press, 1991. Pp. x + 163.